Lean and Green strategy: the Lean and Green House and maturity deployment model. (10th March 2016) - Verrier, Brunilde; Rose, Bertrand; Caillaud, Emmanuel
Abstract: Industrial firms are facing increasing environmental and societal challenges in order to sustain their processes. The association of Lean manufacturing to Green concerns has therefore grown in both the industrial and academic fields over the last decade. Following on from the "Lean and Green Project", this paper intends to enhance previous studies by giving an implementation structure to a Lean and Green methodology based on the seeking and eradication of wastes in production processes. A state of the art featuring main scientific contributions and industrial best practices of Toyota is presented, followed by an in-depth analysis of the synergies between Lean and Green wastes, and the tools that may eliminate them. The results are gathered and highlighted in an original Lean and Green house. The last section presents a detailed CMMI-based Lean and Green maturity model.